2006
DOI: 10.1177/160940690600500401
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocity and Constructions of Informed Consent: Researching with Indigenous Populations

Abstract: In this article, the authors present a discussion of institutional review boards and potential challenges qualitative researchers may face when presenting human subjects research proposals to these boards for approval. In particular, they focus on issues of consent and reciprocity with Indigenous populations, whose culture and traditions might be quite different from those review boards typically see. After presenting these issues, the authors close with a framework that can be used as a guide for ethical cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 11 publications
0
22
0
1
Order By: Relevance
“…She notes that deciding on a topic or purpose of research should reflect the individual researcher's capacity to give back and assist their people. Kovach places emphasis on the point that reciprocity is often achieved through cultural protocols specific to a tribe, such as the Cree practice of giving tobacco as a gift signifying respect and reciprocity (127; see also Ellis and Earley 2006).…”
Section: Reciprocity As Giving Backmentioning
confidence: 99%
“…She notes that deciding on a topic or purpose of research should reflect the individual researcher's capacity to give back and assist their people. Kovach places emphasis on the point that reciprocity is often achieved through cultural protocols specific to a tribe, such as the Cree practice of giving tobacco as a gift signifying respect and reciprocity (127; see also Ellis and Earley 2006).…”
Section: Reciprocity As Giving Backmentioning
confidence: 99%
“…As comprehensive and varied as much of the research in ESL is, little of what has been written addresses the ethical considerations inherent in and raised by ESL research. In contrast, ethical considerations for research are being discussed in various other disciplines such as medicine and nursing (Edwards, Lilford, Thornton, & Hewison, 1998;Turale, 2006), psychology and psychological counseling (Fisher, 2004;Stuart, 1998;West, 2002), Aboriginal studies (Ellis & Earley, 2006;Piquemal, 2001), and anthropology (Gottlieb, 1997). By extension, therefore, it seems appropriate that ethical issues in ESL research should also be identified and examined, especially because much of the research in ESL is conducted by teacher-researchers and/or researchers in countries where ethical concerns may not be addressed formally or by encompassing human 2 JOANNA KOULOURIOTIS rights legislation.…”
mentioning
confidence: 99%
“…• Formulism: an over-reliance on standardised, 'tick-the-box' analyses that mask the complexity of the social context within which research takes place and confines Indigenous philosophies and practices to a narrow sub-set of standardised, heavily proscribed protocols (Hammersley, 2006). • Individualism: privileging autonomous research participants, which leads to informed consent processes that problematise collective decision-making and informed consent protocols (Ellis and Earley, 2006;Glass and Kaufert, 2007;Piquemal, 2000;Wax, 1991).…”
Section: Indigenous Critique Of Research Ethics Boardsmentioning
confidence: 99%